MONEY MULE RECRUITMENT AMONG UNIVERSITY STUDENTS IN MALAYSIA: AWARENESS PERSPECTIVE - Vedamanikam, Mohanamerry; Chethiyar, Saralah Devi Mariamdaran (PUPIL: International Journal of Teaching, Education and Learning, 2020)
Money laundering is perceived as a global threat with funds sourced from illegal and fraudulent activities. Money mules are recruited by criminal networks in money laundering chain, positioned between actual criminal and the illicit funds, enabling the criminals to be anonymous and non-visible to the detection of law enforcement. Job vacancy with various positions are offered with attractive financial rewards and work flexibility and the criminal elements are hidden behind the job criteria. Awareness on job criteria and the hidden criminal elements is a crucial factor in job acceptance. This study examines recruitment anatomy of students as money mules and job acceptance decisioning from awareness perspective. Library research methodology was employed in this research by reviewing existing research works on money mule recruitment to identify the underlying reasons and lapses in money mule recruitment and statistical analysis on the reported money mule cases. Based on the examination, students are captivated to attractive job packages and accept the offer without being aware of the criminal activity at the background and directly expose them to enforcement actions. Incrementing statistics sets the scene of scarcity in the perspective of awareness on job criteria among students and crucial for students to assess and consciously decide on the acceptance and avoid victimized by the criminal networks.